2019
DOI: 10.1016/j.vetpar.2019.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of Giardia duodenalis cysts in immunosuppressed CF-1 mice

Abstract: This study developed and evaluated Giardia duodenalis cyst propagation using a dexamethasone immuno-suppressed CF-1 mouse model as an alternative to a previously described Mongolian gerbil model. The CF-1 mouse model shed significantly more cysts per animal during a 16 to18 h collection period compared to the gerbil (averages: 7.8 × 10 6 cysts/CF-1 mouse and 2.5 × 10 6 cysts/gerbil). In addition, the patency period for this model differed from both G. muris in mice and G. duodenalis in gerbils in that cysts we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…The elimination of the first cysts of G. duodenalis in MS1 and MS2 groups occurred on the 6th dpi. This result is in agreement with Buret et al (1991), who also reported this pre-patency period; however, it differs from other studies that report elimination of cysts from the 3rd dpi (Pavanelli et al, 2018;Ware & Villegas, 2019). Some studies show that this period can vary from one to two weeks (Astiazarán-García et al, 2000;Soares et al, 2008).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The elimination of the first cysts of G. duodenalis in MS1 and MS2 groups occurred on the 6th dpi. This result is in agreement with Buret et al (1991), who also reported this pre-patency period; however, it differs from other studies that report elimination of cysts from the 3rd dpi (Pavanelli et al, 2018;Ware & Villegas, 2019). Some studies show that this period can vary from one to two weeks (Astiazarán-García et al, 2000;Soares et al, 2008).…”
Section: Discussionsupporting
confidence: 87%
“…Cysts of G. duodenalis BIV did not infect Balb/c and C57BL/6 mice, even with inoculum of 10 4 parasites. Infection with cysts in these two lineages was reported in malnourished C57BL/6 (Bartelt et al, 2013), in BALB/cAnUnib Specified Pathogen Free (SPF) (Nakada et al, 2018), and also in immunosuppressed CF1 heterogeneous mice (Ware & Villegas, 2019), indicating that nutritional status and other environmental factors during the maintenance of mice directly influence their capacity to resist to pathogens (Mizutani et al, 2017;Vaidya, 2017). The host's immune response is also a determining factor for infection.…”
Section: Discussionmentioning
confidence: 99%